Wide electrochemical stability window of NaClO4 water-in-salt electrolyte elevates the supercapacitive performance of poly(3,4-ethylenedioxythiophene) - Jha, Plawan Kumar; Kochrekar, Sachin; Jadhav, Ashwini; Lassfolk, Robert; Salomäki, Mikko; Mäkilä, Ermei; Kvarnström, Carita (Elsevier BV, 2025)
Water-in-salt electrolytes (WiSEs) have emerged as the primary preference in the domain of aqueous-based supercapacitors, thanks to their wide electrochemical stability window (ESW > 1.23 V). Here, we have chemically synthesized a unique lettuce coral-like structure of tosylate doped-poly(3,4-ethylenedioxythiophene) (PEDOT-tos) and tested it for supercapacitor application in a 17 molal (m) NaClO4 WiSE, achieving an ESW of 1.9 V. The energy and power densities (E-d and P-d) of our PEDOT-tos supercapacitor are as high as 14 Wh kg(-1) and 7210 W kg(-1), respectively, with over 80 % capacitance retention after 10,000 continuous Galvanostatic charge-discharge cycles. The NaClO4 WiSE increases the E-d and P-d of PEDOT by several folds compared to traditional H2SO4 electrolyte. This work encourages the exploration of a suitable combination of a PEDOT-based composite material and WiSE for high-performance supercapacitors.